# Simplify the fraction (3+ 1/x)/(9-1/x^2)

### 2 Answers | Add Yours

We have to simplify: (3+ 1/x)/(9-1/x^2)

(3+ 1/x)/(9-1/x^2)

=> (3 + 1/x)/(3 - 1/x)(3 + 1/x)

=> 1/(3 - 1/x)

=> x/(3x - 1)

**The required simplified form is x/(3x - 1)**

We'll multiply both numerator and denominator by the largest denominator, namely x^2:

(3x^2 + x^2/x)/(9x^2 - x^2/x^2) = (3x^2 + x)/(9x^2 - 1)

The difference of two squares from denominator returns the product:

(9x^2 - 1) = (3x-1)(3x+1)

We'll factorize the numerator by x:

(3x^2 + x)/(9x^2 - 1) = x(3x+1)/(3x-1)(3x+1)

We'll divide the fraction by (3x+1):

x(3x+1)/(3x-1)(3x+1) = x/(3x-1)**Therefore, simplifying the given fraction, we'll get: x/(3x-1).**